2014
DOI: 10.1002/fsn3.89
|View full text |Cite
|
Sign up to set email alerts
|

The characterization of the physicochemical and sensory properties of full‐fat, reduced‐fat and low‐fat bovine, caprine, and ovine Greek yogurt (Labneh)

Abstract: Concentrated/Greek yogurt or Labneh is a semisolid food produced from yogurt by eliminating part of its water and water-soluble compounds. Today's world is geared toward the production of lower fat foods without compromising the texture and flavor of these products. The objective of this study was to characterize the physicochemical and sensory properties of bovine, caprine, and ovine Labneh with different fat levels. Bovine, caprine, and ovine milks were used to produce two batches of full-fat (∼10%), reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
24
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 17 publications
8
24
1
Order By: Relevance
“…However, a lower consumption (<5 servings per week) of Labaneh did not show any significant association with CRC. Labaneh is a fermented dairy product prepared from yogurt that has been strained in cloth bags to eliminate water and water soluble compounds, mainly whey protein, resulting in a relatively thick consistency, at the same time as preserving a distinctive, sour taste . Labaneh is a traditional food item in Jordan, Lebanon, Middle East and the Balkan regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a lower consumption (<5 servings per week) of Labaneh did not show any significant association with CRC. Labaneh is a fermented dairy product prepared from yogurt that has been strained in cloth bags to eliminate water and water soluble compounds, mainly whey protein, resulting in a relatively thick consistency, at the same time as preserving a distinctive, sour taste . Labaneh is a traditional food item in Jordan, Lebanon, Middle East and the Balkan regions.…”
Section: Discussionmentioning
confidence: 99%
“…However, a lower consumption (<5 servings per week) of Labaneh did not show any significant association with CRC. Labaneh is a fermented dairy product prepared from yogurt that has been strained in cloth bags to eliminate water and water soluble compounds, mainly whey Chi-squareD for difference between total cases and controls = 0.193; chi-squared for difference between male cases and controls = 0.174; chi-squared for difference between female cases and controls = 0.486. protein, resulting in a relatively thick consistency, at the same time as preserving a distinctive, sour taste (31)(32)(33) .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, fermented goat's milk products could represent a good opportunity to increase the supply of dairy products with greater nutritional value (Atamian, Olabi, Baghdadi, & Toufeili, ; Eissa, Mohamed Ahmed, Yagoub, & Babiker, ; Eissa, Babiker, & Yagoub, ; Ribeiro & Ribeiro, ).…”
Section: Introductionmentioning
confidence: 99%
“…In a different study, Atamian et al. () demonstrated through sensory studies that consumer perception of sensory parameters is highly sensitive to sensory attributes. Sensory qualities are known to have clear relationship with product quality, consistency, product development, or consumer acceptance.…”
Section: Introductionmentioning
confidence: 99%
“…Ng'ong 'ola-Manani et al (2014) determined the sensory properties of fermented pastes of soybeans and soybean-maize blends and successfully established the factors driving consumer liking. In a different study, Atamian et al (2014) demonstrated through sensory studies that consumer perception of sensory parameters is highly sensitive to sensory attributes. Sensory qualities are known to have clear relationship with product quality, consistency, product development, or consumer acceptance.…”
Section: Introductionmentioning
confidence: 99%